Penerapan Teknologi Aquaponik Sebagai Upaya Peningkatan Gizi Keluarga Di Desa Wisnu - Firdaus, Anzar Alfat; Maressa, Reyne Ishka; Karimah, Aghnini Fitri; Setiawan, Budi; Prayitno, Muh. Rizki Hariz; Priharyono, Pandu Widya; Wicaksono, Ilham Bayu; Wahyuda, Syefa Maulana; Ayuni, Nurani Ira; Isnaeni, Nur; Meruya, Syifa Kamila; Handayani, Siti (Universitas Tidar, 2025)
This community service program aimed to introduce aquaponic technology as a solution to improve family nutrition in Wisnu Village, Watukumpul Subdistrict, Pemalang Regency. The activities were carried out in four stages: presentation, discussion, hands-on practice, and follow-up assistance and evaluation. Residents were actively involved throughout the entire process. A total of 13 aquaponic units were successfully constructed using simple materials. Catfish fingerlings measuring 7–8 cm were provided by the Department of Marine and Fisheries of Pemalang Regency, while water spinach (Ipomoea aquatica) began to be harvested in the fourth week. Initial monitoring showed that the average fish length increased from 7.5 cm to 12 cm within three weeks. The results indicate that aquaponic technology is an appropriate and practical solution for utilizing household yards and providing nutritious food independently at the household level.